Effect of music therapy on the anxiety levels and pregnancy rate of women undergoing in vitro fertilization-embryo transfer: A randomized controlled trial - ÖZÇELİK, SEMANUR KUMRAL (W B SAUNDERS CO-ELSEVIER INC, 2017)
Purpose: The aim of this study was to determine the effect of music therapy on the anxiety levels and pregnancy rates of women who underwent in vitro fertilization-embryo transfer. Methods: This prospective randomized controlled trial was conducted with 186 infertile women who presented to the In Vitro Fertilization Unit at the American Hospital in Turkey between April 2015 and April 2016. The infertile women who met the inclusion criteria were assigned to the music therapy group or the standard therapy group through block randomization. The study data were collected using the Personal Information Form, and State-Trait Anxiety Inventory. Early treatment success was determined by serum beta human chorionic gonadotrophin levels seven or ten days after the luteal day zero. For the analysis, descriptive statistics, chi-square test, Fisher's exact test, independent sample t-test were used. Results: After the embryo transfer, the mean state anxiety scores decreased in both groups, and the mean trait anxiety score decreased in the music therapy group; however, the difference was not statistically significant (p > 0.05). Clinical pregnancy rates did not differ between the music (483%) and standard (46.4%) therapy groups. Conclusion: After the two sessions of music therapy, state and trait anxiety levels decreased and pregnancy rates increased, but the difference was not significant Therefore, larger sample sizes and more sessions are needed to evaluate whether music therapy has an effect on clinical outcomes. (C) 2017 Elsevier Inc. All rights reserved.
Keywords: Infertility In vitro fertilization; Music therapy; Anxiety; Nursing; Turkey; INFERTILITY TREATMENT; ALTERNATIVE MEDICINE; MENTAL-HEALTH; DISTRESS; COMPLEMENTARY; PREVALENCE; STRESS; IVF; METAANALYSIS; ADJUSTMENT